1982
DOI: 10.1002/j.1460-2075.1982.tb01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural homologies among type I restriction-modification systems.

Abstract: Structural homologies among different restriction systems of Escherichia coli and several Salmonella species have been investigated by immunological methods using antibodies prepared against two subunits of the E. coli K12 restriction enzyme, and by DNA hybridization experiments using different fragments of the E. coli K12 hsd genes as probes. The results with both techniques show a strong homology between the E. coli K12 and B restriction‐modification systems, weaker but nevertheless marked homology between E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 38 publications
0
59
0
Order By: Relevance
“…Therefore, classification of HsdM families based on amino acid sequence similarity alone has the potential drawback of eventually generating an enormous number of type I R-M families. Analyses based on other criteria, such as allelic complementation and immunological cross-reactivity (Fuller-Pace et al, 1985;Murray et al, 1982;Suri & Bickle, 1985), may be able to place distantly related type I systems (e.g. the type ID and type 'IF' systems) into the same family; however, analyses performed on such diverse taxa may be problematic.…”
Section: Family Classification Of the C Jejuni Hsd Locimentioning
confidence: 99%
“…Therefore, classification of HsdM families based on amino acid sequence similarity alone has the potential drawback of eventually generating an enormous number of type I R-M families. Analyses based on other criteria, such as allelic complementation and immunological cross-reactivity (Fuller-Pace et al, 1985;Murray et al, 1982;Suri & Bickle, 1985), may be able to place distantly related type I systems (e.g. the type ID and type 'IF' systems) into the same family; however, analyses performed on such diverse taxa may be problematic.…”
Section: Family Classification Of the C Jejuni Hsd Locimentioning
confidence: 99%
“…Of fundamental influence in our understanding of type I R-M systems has been the demonstration that these enzymes can be considered as members of a family within which the subunits of different enzymes are interchangeable. It came as a surprise, however, that alleles at this locus, in particular those specifying EcoAI in E. coli strain 15T − , encode sufficiently dissimilar type I R-M systems to warrant their separation into a different family (Murray et al, 1982). The initial evidence came from hybridization screens of bacterial DNAs and serological screens of bacterial extracts.…”
Section: The Immigration Control Region and The Family Conceptmentioning
confidence: 99%
“…The enzyme was purified by a series of column chromatography steps on DEAE-Sephacel, gel filtration on Sephacryl S-200, heparin agarose and lastly on ATP-agarose. The purification was monitored by the DNA dependent, S-adenosylmethionine (AdoMet) dependent ATPase activity of the enzyme as described in (12) as well as by immunoblotting (13) using antibodies raised against the hsdR and hsdM subunits of EcoK as previously described (7,11). In vitro DNA methylation Methylation of DNA by EcoD was carried out using H-methylAdoMet (Amersham, 64-74 Ci/mmol) as described in (14) with some modifications (11).…”
Section: Purification Of Ecodmentioning
confidence: 99%
“…Further, DNA hybridisation experiments using probes derived from the E. coli K12 hsd region have suggested a close similarity between the hsdR and hsdM genes of E. coli K12 and those of several other systems, confirming their allelic nature. Interestingly enough, these experiments showed that there was no such strong homology between the different hsdS genes (7).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation